페루 도시 빈민지역 청소년의 비만에 따른 식생활 및 건강요인의 차이 - 정혜경(Hye-Kyung Chung); 이해영(Hae-Young Lee); 김진리(Jin Ri Kim); 남은우(Eun Woo Nam) (Korean journal of community nutrition, 2018)
Objectives: This study examined the differences in dietary life and health related factors, such as drinking behavior, exercise and leisure activities, mental health, and subjective perception for oneself according to obesity in poor urban Peruvian adolescents. Methods: A total of 1,532 Peruvian adolescents were selected from six schools in poor regions using stratified random sampling. The subjects were classified into two groups based on their BMI: 'normal weight group (NW group=980)' or 'overweight and obese group (OWOB group=293)'. The differences in the general characteristics, dietary life, drinking behavior, physical activity and leisure, mental health and subjective perception of oneself in the two groups were compared. ${χ}^2$ analysis and independent sample t-test were performed using the SPSS program ver. 24. Results: For the total and male students, the frequency of breakfast and dinner were significantly lower in the OWOB group than in the NW group (all p<0.001). For total and female students, the percentage of subjects who received nutrition education was significantly higher in the OWOB group than in the NW group (all p<0.05). For total students, the percentage of subject who exercised more than five days/week was lower in the OWOB group than in the NW group (p<0.05). For the total and female students, the subjective health status was worse in the OWOB group than in the NW group (all p<0.05). The subjective body image was significantly different between the OWOB group and NW group in the total, male and female subjects (all p<0.001). Conclusions: The frequency of meals and exercise, and the subjective perceptions of the health status and body image differed according to obesity in poor urban Peruvian adolescents. Therefore, a school-based intervention program focused on regular meal and exercise, and adequate subjective perceptions for health status and body image need to be developed to prevent adolescent obesity.